The relationship among positive body image, body esteem, and eating attitude in Iranian population - Sharif-Nia, Hamid; Sivarajan Froelicher, Erika; Gorgulu, Ozkan; Osborne, Jason W.; Błachnio, Aleksandra; Rezazadeh Fazeli, Azadeh; Goudarzian, Amir Hossein; Kaveh, Omolhoda (Frontiers in Psychology, 2024)
Background and aim The correlation between eating attitudes, positive body image, and body esteem is a pivotal area of research that has garnered substantial attention in recent years, given its implications for both mental and physical well-being. The objective of this study was to examine the interplay between positive body image, body esteem, and eating attitudes within an Iranian population. Materials and methods This study employed a cross-sectional study design and was conducted in the year 2022. A convenience sample of 752 participants residing in Tehran, Iran, was included in the study. The data collection tools were comprised of a demographic registration form, the Adolescence/Adults Scale (PBIAS), the Eating Attitudes Test (EAT), and the Body Esteem Scale (BES) as measurement instruments. Results Mean age of participants was 26.36 (SD = 8.49). Significant relationships were found among positive body image (B = − 0.095, β = −0.150, p < 0.001), and body esteem (B = 0.175, β = 0.149, p < 0.001) with eating attitudes. Conclusion These findings suggest that individuals with positive body image and high body esteem may have healthier eating attitudes, while those with negative body image and low body esteem may be more likely to have unhealthy eating attitudes.